2020
DOI: 10.2169/internalmedicine.3625-19
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension and Hereditary Hemorrhagic Telangiectasia Related to an <i>ACVRL1</i> Mutation

Abstract: Pulmonary hypertension and hereditary hemorrhagic telangiectasia (HHT) have an association mediated by activin A receptor type II-like 1 (ACVRL1) gene pathogenic variants. A 30-year-old woman was previously admitted to a hospital due to lung hemorrhage, and was diagnosed with pulmonary hypertension, but stopped follow-up visits. At 48 years of age, she was admitted to our hospital and was diagnosed with HHT. Genetic testing revealed an ACVRL1 pathogenic variant. After the initiation of pulmonary vasodilator tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Many of these HHT patients have secondary PH, often as a result of high-output cardiac failure secondary to hepatic arteriovenous malformations (AVMs) [8,10,80,82]. A smaller proportion of patients, about 1%, have heritable or primary PH; this is usually seen with the ACVRL1 mutation (HHT type 2) [83][84][85][86]. The coexistence of PAVMs and PH poses a clinical dilemma, as there is a paucity of data examining the evolution of PH following PAVM embolization.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these HHT patients have secondary PH, often as a result of high-output cardiac failure secondary to hepatic arteriovenous malformations (AVMs) [8,10,80,82]. A smaller proportion of patients, about 1%, have heritable or primary PH; this is usually seen with the ACVRL1 mutation (HHT type 2) [83][84][85][86]. The coexistence of PAVMs and PH poses a clinical dilemma, as there is a paucity of data examining the evolution of PH following PAVM embolization.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…In cases where the effect of embolization is uncertain, temporary occlusion of the feeding artery can be performed with a balloon occlusion catheter while monitoring the cardiovascular response, to predict the risk of pulmonary hemodynamic changes prior to embolization [58]. There may also be a role for endothelin-receptor antagonists to mitigate worsening of PH following PAVM embolization in at-risk patients, though further study is needed [86].…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…It is known that ACVRL1 is one of the genes affected by germline mutations identified in patients with pulmonary arterial hypertension 28 . Germline mutations of ACVRL1 also cause hereditary hemorrhagic telangiectasia, a dominant autosomal vascular dysplasia, and PH is recognized as a severe complication of this disease 40,41 . It has been reported that ACVRL1 mutations in hereditary hemorrhagic telangiectasia led to a loss of function 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Variant p.Arg484Gln impacts a conserved surface-exposed residue located in helix αI of the kinase C-lobe, and encodes a catalytically inactive ALK1 mutant 86 . Mutations in this region are associated with HHT2, an increased incidence of pulmonary arterial hypertension [87][88][89] , and with other ALK family-associated diseases such as brachydactyly type A2 (ALK6) 90,91 and Loeys-Dietz syndrome (ALK5) 92,93 . ACVRL1 p.Arg484Gln has also been identified in HHT2 94 and in childhood-onset pulmonary arterial hypertension 95 .…”
Section: Variants In Acvrl1 and Other Mutation-intolerant Mendelian V...mentioning
confidence: 99%